Antibacterial activity, antioxidant potential, total phenolic and flavonoids of three plant species of Rubiaceae from Banggai Island, Indonesia - Praptiwi Praptiwi; Diah Sulistiarini; Ersaliany Nurul Pratiwi Qodrie; Deni Sahroni (Society for Indonesian Biodiversity, 2021)
Abstract. Praptiwi, Sulistiarini D, Qodrie ENP, Sahroni D. 2021. Antibacterial activity, antioxidant potential, total phenolic and flavonoids of three plant species of Rubiaceae from Banggai Island, Indonesia. Biodiversitas 22: 2773-2778. The present study was carried out to study the antioxidant and antibacterial potential of different plant parts (stems, leaves, and fruit) of the family Rubiaceae (Timonius celebicus, Psychotria celebica, Gardenia mutabilis) collected from the Banggai Islands. Screening of antibacterial activity against Staphylococcus aureus and Escherichia coli and antioxidant potential was carried out by Thin Layer Chromatography- Bioautography. Determination of IC50 and Minimum Inhibitory Concentration (MIC) was carried out by microdilution in a 96-well microplate. Total phenolic and total flavonoid content was determined by the colorimetric method. Total phenolic (TPC) and total flavonoid content (TFC) was varied from 29.78-380.99 mg GAE/g extract and 105.61-841.18 mg QE/g extract, respectively. The antioxidant capacity of three plant species was varied from moderate to very strong. Antioxidant Activity Index (AAI) was found more affected by TFC than TPC. The antibacterial activity of the extract against E. coli was weak, while some extracts have moderate antibacterial activity against S. aureus